ALTERAÇÕES QUÍMICAS DO SOLO E RESPOSTA DA VIDEIRA ‘NIAGARA ROSADA’ À APLICAÇÃO DE GESSO AGRÍCOLA PONTA GROSSA - PR - Blum, Julius (2008)
Gypsum applied on the soil surface reduces subsoil Al3+ toxicity and increases the Ca2+ and S-SO42- levels, promoting better development of plant roots. Gains in productivity has observed with the use of gypsum in annual and perennial crops, but lacking studies regarding to gypsum application on grapevines. The aim of this study was to evaluate the effect of gypsum on soil chemical attributes and the production of the ‘Niagara Rosada’ grape. A field trial was carried out in a 8 years old orchard, on a dystrophic clayey Rhodic Hapludox at Ponta Grossa, Parana State, Brazil. The soil had low acidity and sufficient nutrient levels in the top soil (0-20 cm), and high concentration of exchangeable Al3+ in subsurface. A randomized block design was used and five gypsum rates were surface applied (0, 3, 6, 9 and 12 t ha-1), with four replications. After 8 months of the application, there was an increase in soil pH below 20 cm and decrease in the Al3+ content. These effects were intensified after 20 months. Was an increase in Ca2+ and S-SO42- levels in all soil profile after gypsum application. Movement of Mg2+ from the top soil to deeper layers occurred after 8 months, and this effect was intensified after 20 months. The improvement on soil fertility had no effect on grape nutrition in the first year. There was a decrease in leaf magnesium concentration at the second year. Gypsum application had negative effect on fruit production due to leaching of exchangeable Mg2+ from the topsoil. Chemical changes at layer 0-20 cm depth were better correlated with the plant nutrition. There was correlation between the Ca2+/Mg2+ ratio, and saturation and concentration of Mg2+ in the soil with foliar concentration of magnesium and grape productivity. The critical level of Mg2+ in the soil (90 of relative production) was 42 mmolc dm-3. The Ca2+/Mg2+ ratio and the percentage of Mg2+ in CEC at pH 7 were more appropriate than just the concentration of Mg2+ for the diagnosis of the nutrient in the soil. A Ca2+/Mg2+ ratio of 1.9 and 25 of magnesium in CEC at pH 7 were established for 90 relative production. The Ca/Mg ratio was better to nutritional diagnosis on plants than the magnesium concentration. A 2 Ca2+/Mg2+ ratio in leaves was the critical level for 90 relative production. The application of gypsum caused increase in soluble solids in the berries, ameliorating grape quality.